The Effect Of Managerial Ownership, Institutional Ownership, Growth Opportunity And Profitability On Accounting Conservatism - Widaryanti Widaryanti (GOVERNORS, 2022)
This studi aims to analyze the effect of Manajerial Ownership, Institutonal Ownership, Growth Opportunity and Profitability on Accounting Conservatism. With a sample of 165 manufacturing companies listed on the Indonesia Stock Exchange in 2017-2019 selected using the purposive sampling method. The data obtained in this study used the documentation method. With multiple regression analysis method. Data collection method by understanding secondary data obtained from external sources and financial reports of producers listed on the Indonesia Stock Exchange. The results of this study are that managerial ownership has a negative and insignificant effect on accounting conservatism. From these results it can be said that although management is the shareholder and owner, there is no significant effect. Not all executives in the company own shares in the company. As a result, management tends to apply accounting principles while minimizing profits. Institutional ownership and growth opportunity have no effect on accounting conservatism. These results indicate that all manufacturers apply the precautionary accounting principle. Profitability has a positive effect on accounting conservatism.